1.[(M-2n)^3]^2·(2n-m)^52.m^2·()^2=M^()·m=(m^3)^2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 00:34:59
1.[(M-2n)^3]^2·(2n-m)^52.m^2·()^2=M^()·m=(m^3)^21.[(M-2n)^3]^2·(2n-m)^52.m^2·()^2=M^()·m=(m^3)^21.[(
1.[(M-2n)^3]^2·(2n-m)^52.m^2·()^2=M^()·m=(m^3)^2
1.[(M-2n)^3]^2·(2n-m)^5
2.m^2·()^2=M^()·m=(m^3)^2
1.[(M-2n)^3]^2·(2n-m)^52.m^2·()^2=M^()·m=(m^3)^2
1. [(M-2n)^3]^2·(2n-m)^5
=(m-2n)^6×[-(m-2n)^5]
=-(m-2n)^11
2. m^2·(m²)^2=M^(5)·m=(m^3)^2
-(M-2N)五次方 看不懂
2(m-n)^2-(m+n)(m-2n)-3n(n-m) 公因式(n-m)
m/n=5/3,求(m/m+n)+(m/m+n)-(n^2/m^2-n^2)
已知m/n=5、,求(m/(m+n))+(m/(m-n))-(n^2/(m^3-n^2))
(m+2n)(2m+n)-(3m-n)(m+2n)
(3m-4n)(4n+3m)-(2m-n)(2m+n)
计算(3-m+n)*(3+m-n)-(2-m+n)*(2+m-n)
因式分解:(m+n)^3+2m(m+n)^2+m^2(m+n)
计算4(m+n)^2·(-m-n)^3-(m+n)(-m-n)^4+5(m+n)^5
若(m+n)^2-mn(m+n)=(m+n)·M,则M是() A.m^2+n^2 B.m^2-mn+n^2 C.m^2-3mn+n^2 D.m^2+mn+n^2
(1),(-m-n)(-m+n) (2),(-m+n)(m-n)
[(m-n)^2*(m-n)^3]^2/(m-n)^4
[(m-n)^2*(m-n)^3]^2/(m-n)^4
3m(m-n)-2n(m-n)的平方
因式分解(n-m)^3(m-n)^2-(m-n)^5
(m-n)2(n-m)3(n-m)4化简
(n-m)^3×(m-n)^2-(m-n)^5
计算(m+n)^3-(n+m)(m-n)^2
(m-n)^3(n-m)^2(m-n)=_____